Adoption of Internet of Things in Water Drinking Reminder System - Ng, Hui Xin; Malathy, Batumalay; Rajermani, Thinakaran (INTI International University, 2022)
Drinking water is essential for human beings to continue surviving. Everyone knows the importance of water, but people tend to forget to drink water when they are busy on doing their work. In addition, with the current pandemic Covid-19, the importance of drinking enough water is vital. There is water drinking reminder application available but might not be effective in recording the right amount of water consumed. A system using Internet of Things (IoT) – water level monitoring system is proposed here. It is a water drinking reminder system which will detect the volume of water consumed. The system will alert the person to drink water if the water level remained the same for a long time by sending a pop-up notification through the phone. Background study has been conducted to better understand the existing water level monitoring systems. Information has been collected through interview and questionnaire, and the system has gone through several testing. Imposing the system will encourage people to drink water regularly and maintain a healthy body.